Dux Is Dispensable for Skeletal Muscle Regeneration: A Study Inspired by a “Red Flagged” Publication and Editorial Oversight - Kenric Chen; Erdong Wei; Ana Mitanoska; Micah D. Gearhart; Michael Kyba; Darko Bosnakovski (Cells)
Double homeobox (DUX) genes are key embryonic regulators that are silenced after the early cleavage stages of embryogenesis. Aberrant expression of DUX4 in skeletal muscle is linked to facioscapulohumeral muscular dystrophy (FSHD). A recent study reported that Dux, the murine ortholog of DUX4, contributes to the dystrophic phenotype in mdx mice, a Duchenne muscular dystrophy (DMD) model, and that its deletion enhances muscle regeneration by reducing oxidative stress. However, convincing evidence of Dux expression in either intact or injured muscle of wild-type (WT) and mdx mice remains lacking, raising questions about its role in muscle homeostasis. To investigate this, we assessed Dux expression in WT and mdx mice and used Dux knockout (DuxΔ/Δ) mice to evaluate its function during regeneration following cardiotoxin (CTX)-induced injury. Contrary to prior reports, Dux was not expressed in either WT or mdx mice. Moreover, Dux deletion did not enhance muscle regeneration or affect the expression of the oxidative stress regulator Nrf2 following CTX injury. Lastly, we confirmed that neither DUX4 nor its target genes were induced in muscle biopsies from DMD patients, excluding a role for DUX4 in DMD pathology. Collectively, our results demonstrate that Dux does not impact skeletal muscle regeneration or DUX4 contribution to the DMD dystrophic phenotype, directly challenging the conclusions of a previously published study. We comment on issues of editorial oversight that led to the publication of that study and highlight the deleterious impact of the growing wave of fraudulent publications.